Editorial Commentary: Femoral Version and Capsular Thickness Analysis in Hip Preservation Surgery-Surgical Indications Are as Important as Surgical Technique - Harris, Joshua D (Arthroscopy, 2024)
Optimal treatment of patients with femoroacetabular impingement syndrome requires both thoughtful decision-making and skillful operative technique. Traditional evidence-based literature and routine clinical practice overemphasize the role of the alpha angle on the femoral side and lateral center edge angle on the acetabular side. Femoral and acetabular version are critical values that influence outcomes and warrant measurement and consideration. Without version analysis, an uniformed, possibly poor, decision may be made. The literature and clinical practice also place dichotomous emphasis on labral (torn/intact) and capsular (torn/intact) integrity, with minimal appreciation of the morphological details of both. Not all capsules are created equal. "Normal" capsule thickness is a nebulous concept, with thinner anterior capsules more prone to anterior instability. Intuitively, it biomechanically stands to reason that excessive femoral anteversion (and excessive anterior cranial and central acetabular version) would place additional stress on the anterior capsule. Excessive femoral anteversion is associated with a thinner anterior capsule. Whether the latter is a reactive process (implies causation) or simply 2 concordant metrics (only correlation) has yet to be determined. In patients with nonarthritic hip pain, comprehensive quantitative consideration of both femoral and acetabular version and capsular thickness determines the optimal hip preservation procedure. Surgical indications are as important as surgical technique.